Effect of high-pressure treatment on taste and metabolite profiles of ducks with two different vinasse-curing processes. (March 2018) - Lou, Xiaowei; Ye, Yangfang; Wang, Ying; Sun, Yangying; Pan, Daodong; Cao, Jinxuan
Abstract: The effect of high-pressure (HP) (0.1, 150 and 300 MPa, 15 min) on taste profiles of vinasse-cured ducks was investigated; the metabolite profiles were determined using 1 H NMR. HP at 150 MPa increased the taste intensity of products compared with the controls, while HP at 300 MPa did not further improve their taste compared with 150 MPa treated samples. The metabonome of vinasse-cured ducks was dominated by 27 metabolites. HP increased amino acids, glucose, alkaloids and organic acids, but decreased inosine monophosphate and its derivatives, compared with the controls. The increments of metabolites in vinasse-dry-cured duck were higher than those in vinasse-wet-cured duck. The change of metabolites could be related to the enzyme activity, the degradations of proteins, sugars and nucleotides, and the permeation from vinasse-curing agents to duck meat. These findings suggest that 150 MPa treatment was effective to improve the taste of vinasse-cured duck. Graphical abstract: Highlights: The metabolite profile of vinasse-cured duck was dominated by 27 metabolites. Amino acids, glucose, alkaloids and organic acid increased under HP. HP improved the taste of vinasse-cured duck. The increase of taste in vinasse-dry-cured duck was higher than wet-cured duck. 150 MPa treatment was effective to improve the taste of vinasse-cured duck.